The safety of available treatments options for neuroendocrine tumors - Faggiano, A; Lo Calzo, F; Pizza, G; Modica, R; Colao, A (Expert opinion on drug safety, 2017)
Neuroendocrine neoplasms (NEN) represent a heterogeneous group of malignancies generally characterized by low proliferation and indolent course. However, about half of the newly diagnosed cases are metastatic and require long-term systemic therapies. Areas covered: This review revises the literature to summarize the current knowledge upon safety of all systemic treatment options available. Thirty three different clinical studies have been considered, including 4 on somatostatin analogues (SSA), 5 on targeted therapies, 10 on peptide receptor radionuclide therapy (PRRT), and 14 on chemotherapy. Expert opinion: SSA are safe and well tolerated without any relevant severe adverse event and very low treatment discontinuation rate. Targeted therapies show a satisfying safety profile. Most adverse events are grade 1-2 and easy manageable with dose reduction or temporary interruption. PRRT is manageable and safe with a low rate of grade 3-4 adverse events. However, severe renal and hematologic toxicity may occur. Chemotherapy is usually considered after previous therapeutic lines. Therefore, these subjects are more susceptible to experience adverse events due to cumulative toxicities or poor performance status. The available systemic treatment options are generally well tolerated and suitable for long-term administration. Cumulative toxicity should be taken in account for the definition of therapeutic sequence.